Chemical constituents and antiviral study of Goniothalamus velutinus - Fasihuddin Badruddin,, Ahmad; Nur Khairun Nisa,, Mohd Sallehuddin; Zaini,, Assim (Ibnu Sina Institute, 2014)
Phytochemical study on the stem barks of Goniothalamus velutinus resulted in the isolation of three compounds identified as goniothalamin (1), pinocembrine (2) and naringenin (3). Their structures were elucidated using various spectroscopic methods especially Fourier Transform Infrared (FTIR), Nuclear Magnetic Resonance (NMR) and gas chromatography-mass spectrometry (GC-MS). Goniothalamin (1) has been isolated from several Goniothalamus spp. but no report on the isolation of (1) from Goniothalamus velutinus. Antiviral properties of (1) against Measles virus showed weak activity compared to positive control, ribavirin